2012
DOI: 10.1016/j.eats.2012.07.006
|View full text |Cite
|
Sign up to set email alerts
|

ORV Arthroscopic Transosseous Bony Bankart Repair

Abstract: Abstract:The arthroscopic treatment of the "bony Bankart lesion" continues to evolve. We present a novel technique that we developed at Orthopaedic Research of Virginia, the "transosseous bony Bankart repair," which incorporates several essential concepts to provide for optimal healing and rehabilitation. We promote arthroscopic repair emphasizing bone preservation, a fracture interface without interposing sutures, the ability to reduce capsular volume, and multiple points of stable glenolabral fixation. Our t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…Since then, numerous arthroscopic techniques to address Bankart fractures have been published. [5][6][7][8][9][10][11][12][13][14] Despite the high incidence (4% to 70%) of bony Bankart lesions after shoulder dislocation, few clinical outcome studies of arthroscopic bony Bankart repair have been published to date. [1][2][3]11,[15][16][17] Most of the published clinical trials focus on the size of the remaining defect, as shown by computed tomography (CT), as well as the influence of fragment reduction and bony healing on postoperative failure and patient satisfaction.…”
mentioning
confidence: 96%
“…Since then, numerous arthroscopic techniques to address Bankart fractures have been published. [5][6][7][8][9][10][11][12][13][14] Despite the high incidence (4% to 70%) of bony Bankart lesions after shoulder dislocation, few clinical outcome studies of arthroscopic bony Bankart repair have been published to date. [1][2][3]11,[15][16][17] Most of the published clinical trials focus on the size of the remaining defect, as shown by computed tomography (CT), as well as the influence of fragment reduction and bony healing on postoperative failure and patient satisfaction.…”
mentioning
confidence: 96%
“…The nail is inserted into a non-articulating portion of the chondral surface of the humeral head, previously described as the optimal starting point to avoid rotator cuff disruption [13,26]. This technique allows the muscular portion of the supraspinatus to be penetrated while sparing the tendinous insertion, as is done in arthroscopic labral repairs [27]. While conceptual concerns exist regarding penetrating the articular cartilage of the humeral head, reports documenting the use of retrograde femoral nails with a starting point through the non-weight-bearing articular cartilage of the distal femur date back over 20 years [28,29] and continue to yield positive results [30].…”
Section: Discussionmentioning
confidence: 99%
“…A possible solution may be transosseous bony Bankart repair, and such techniques have been recently described. Myer and Caldwell 32 and Driscoll et al 12 both described techniques utilizing a primary suture anchor placed medial to the glenoid articular surface, with suture limbs passing in a transosseous fashion through the bony Bankart fracture fragment. Two other suture anchors are then placed superior and inferior to the primary anchor to capture the labrum and capsule.…”
Section: Discussionmentioning
confidence: 99%